Thyroid Tuberculosis in a Child: A Rare Entity - Bodh, Anita; Sharma, Neelam; Negi, Lalita; Chandel, Suman S (Journal of Laboratory Physicians, 2014)
Thyroid tuberculosis is a rare disease even in countries where tuberculosis is endemic. Clinically tuberculosis is not often suspected in cases of thyroid nodule or swelling. We report a case of 11 years female child who presented with a thyroid swelling. Fine-needle aspiration cytology revealed caseating epithelioid granulomas and acid fast bacilli. Patient improved with antitubercular drugs. Tuberculosis may be considered as differential diagnosis of thyroid swelling.
Keywords: Acid fast bacilli; thyroid; tuberculosis